The pronunciation difficulties of Arabic segmental sounds among Malay speakers - Al Qarni, Mansour Dhafer Abdullah; Sharifah Raihan Syed Jaafar,; Shahidi A.H., (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research sought to identify the emphatic and guttural sound pronunciation challenges faced by Malaysian Malays studying in Saudi Arabia. The study sample comprised 16 Malaysian students pursuing in undergraduate and postgraduate degrees in myriad fields at the Islamic University in Madinah. Each participant was required to read two short Arabic passages adopted from Quranic verses and Kitab La Tahzen. In addition, they read and pronounce some phrases involving: 50 contexts, 150 words and 50 short sentences. The results revealed numerous complex consonant sounds in the participants’ perceptions and productions. Denti-alveolar and fricative pharyngeal-glottal sounds, such as /t ت/, /ð ذ/, /sˤ ص/, /dˤ ض/, /ðˤ ظ /, /ħ ح/, /ʕ ع/ and /ɦ هـ/, appeared to be the most challenging Arabic consonants to pronounce, particularly when the sounds are in the medial position of a word. The results further demonstrated that students view Arabic as an essential language, albeit with several challenging consonant sounds. The pharyngeal and pharyngealized consonant phonemes were shown to be arduous for perception and production; however, students perceive the fricative pharyngeal-glottal phoneme contrast to be the toughest Arabic consonant contrast to acquire. It was also discovered that students opine that personal motivation, interaction with native speakers, and radio and television exposure are the most influential determinants of their ability to acquire Arabic consonants. On the contrary, the students reported that individual capabilities like mimicry and musical talent are not as effective in aiding acquisition. The findings of this study validate the specific Arabic consonants that pose a key source of difficulty for learners of the language.